2020
DOI: 10.1108/bpmj-08-2019-0319
|View full text |Cite
|
Sign up to set email alerts
|

Business development through knowledge sharing among members of sectoral committees

Abstract: PurposeThis paper is an empirical study examining how sectoral committees function as knowledge networks within CCIs in Saudi Arabia. It employs the Madinah Chambers of Commerce and Industry (MCCI) branch as a case study. The research examines the influence of individual factors (taking pleasure in helping others, knowledge of self-efficacy, and outcome expectations), and organisational factors (top management support and knowledge sharing culture) on knowledge sharing, to establish whether knowledge sharing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Leaders' role in KS process is to manage the flow of tacit and explicit knowledge, activate internal and external motivations, improve the organisational climate, establish organisational values, empower subordinates and use information technology (IT). This role leverages KS in an empowering and reliable environment that supports learning and innovation, and thus improve overall performance (Aljuwaiber, 2020;Panahi et al, 2013;Tohidinia and Mosakhani, 2010). KS process comprises four stages.…”
Section: Theoretical Background and Hypothesis Formulation 21 Knowledge Management Processesmentioning
confidence: 99%
“…Leaders' role in KS process is to manage the flow of tacit and explicit knowledge, activate internal and external motivations, improve the organisational climate, establish organisational values, empower subordinates and use information technology (IT). This role leverages KS in an empowering and reliable environment that supports learning and innovation, and thus improve overall performance (Aljuwaiber, 2020;Panahi et al, 2013;Tohidinia and Mosakhani, 2010). KS process comprises four stages.…”
Section: Theoretical Background and Hypothesis Formulation 21 Knowledge Management Processesmentioning
confidence: 99%
“…Receiving attention from senior management supports reviewing and implementing ideas and suggestions. A recent study by Aljuwaiber (2020) corroborates this in an investigation of the role of knowledge sharing in business development among members of sectoral committees. The study found that the level of support from senior management affected the willingness to share knowledge and exchange personal expertise.…”
Section: Organizational Communities Of Practices and Their Establishment In Different Organizational Contextsmentioning
confidence: 60%
“…Openness: [18] mentioned that the openness factor is related to change. It is aligned with [19] statement that people motivated to contribute to knowledge usually have pleasure in helping others because they feel involved in solving problems and engaged in intellectual pursuit. People with an openness to help others tend to do new things that challenge them.…”
Section: Knowledge Sharing Drivermentioning
confidence: 62%
“…Knowledge Sharing Drivers [6], [8], [9], [11], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26] Details of the findings can be seen in Table 4 and Table 5. The author extracted the knowledge sharing driver and barrier from each of the literature.…”
Section: Indicators Reference Qtymentioning
confidence: 99%
See 1 more Smart Citation